Aplicação do Problem Based Learning (PBL): uma percepção dos coordenadores dos cursos de Ciências Contábeis - Santos, Marcello Lopes dos (2014)
In today's world, the discussion about teaching is taking place in all spheres, from the earliest teachings graduates. Reports, studies and surveys show that the scenario needs to change and has scheduled several initiatives from both government as private institutions for the changes are positive and bring improvements to the current school. One of the questions that have intrigued researchers are about teaching methods. We all know that traditional methods are saturated and with the advent of new technologies that integrate studies, rapid change is necessary for professionals to monitor all instances in real time. One of the proposals is the problem-based learning, called PBL (Problem Based Learning). In this study, the focus of research is the effectiveness of the implementation of this method looks for the coordination of Institutions of Higher Education of São Paulo, a critical eye and people who are on the frontlines arguing for improvements in the preparation of future professionals in the accounting area